2013
DOI: 10.1016/j.sjbs.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead stress on mineral content and growth of wheat (Triticum aestivum) and spinach (Spinacia oleracea) seedlings

Abstract: Lead (Pb) is the most common heavy metal contaminant in the environment. Pb is not an essential element for plants, but they absorb it when it is present in their environment, especially in rural areas when the soil is polluted by automotive exhaust and in fields contaminated with fertilizers containing heavy metal impurities. To investigate lead effects on nutrient uptake and metabolism, two plant species, spinach (Spinacia oleracea) and wheat (Triticum aestivum), were grown under hydroponic conditions and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 25 publications
9
77
0
1
Order By: Relevance
“…Intercept, linear coefficient (LC), quadratic coefficient (QC) and correlation coefficient (R²) of the regression equation on spindle organization during mitosis, compromising cell division (Kozhevnikova et al, 2009) and to the deficiency in the absorption of macroelements (Lamhamdi et al, 2013) caused by the lower volume of roots.…”
Section: Resultsmentioning
confidence: 99%
“…Intercept, linear coefficient (LC), quadratic coefficient (QC) and correlation coefficient (R²) of the regression equation on spindle organization during mitosis, compromising cell division (Kozhevnikova et al, 2009) and to the deficiency in the absorption of macroelements (Lamhamdi et al, 2013) caused by the lower volume of roots.…”
Section: Resultsmentioning
confidence: 99%
“…Huang and Cunningham (1996) observed that Pb reduced Mg concentrations in shoots of Z. mays and A. artemisiifolia plants. Lamhamdi et al (2013) reported that Pb concentrations higher than 1.5 mM significantly decreased Mg contents in shoots and roots of Triticum aestivum and Spinacia oleracea seedlings.…”
Section: Macronutrient (N P K Ca and Mg) Concentrationsmentioning
confidence: 99%
“…Increased proline biosynthesis has been considered to play an important role in plant tolerance to Pb stress (POURRUT et al, 2011;QURESHI et al, 2007;DUBEY, 2005). Lamhamdi et al (2013) found that proline contents increased in leaves of T. aestivum and S. oleracea when the plants were exposed to increasing Pb concentrations. According to Verbruggen and Hermans (2008), proline contents may vary among species, and their values are up to 100 times higher in stressed plants than those in control ones.…”
Section: Organic Solutesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the imbalance of nutrients and decreasing of plant biomass might be a convenient and reliable symptom of heavy metal toxicity in plants. On the other hand, lead accumulation in plant tissues increases with an increase in the exogenous lead level (Lamhamdi et al 2013). Therefore, plant species with high accumulation ability in their organs are good candidates for heavy metal remediation.…”
Section: Introductionmentioning
confidence: 99%